Decision Making on Divorce for Javanese Women in Indonesia - Devi PUSPITASARI; Jatie. K. PUDJIBUDOJO; Hartanti HARTANTI (Indonesia Strategic Sustainability, 2022)
Javanese society has a philosophy of life that emphasizes harmony, harmony, and acceptance (nrimo) for everything that happens. Javanese marriage firmly places the role of women as the husband's konco wingking responsible for marital harmony, so if there is a conflict or divorce, the woman or wife becomes a party who is seen as negative because they are considered unable to serve their husbands. The divorce rate among Javanese women always increases and is two times higher than that of men (talak). The purpose of this study is to explain the process of making divorce decisions for Javanese women. This study uses an interpretive phenomenological qualitative method with in-depth interview data collection techniques. The technical analysis used is Interpretative Phenomenological Analysis (IPA). The study was conducted on three Javanese women divorced from their husbands. The criteria for the participants are Javanese women who have filed for divorce and have been divorced a maximum of six months before the interview, have children and are employed. The research locations are Kediri and Madiun. The location in the area is chosen because it has a strong Javanese culture. The results showed that the divorce decision-making process for Javanese women was complicated because of the stigma of being a widow. The decision-making process for divorce in Javanese women is influenced by eight factors: children, physical and emotional impacts, friendships and good memories, commitment to marriage, finances, support from friends and family, religiosity and Javanese expectations and ethics.